A case with combined postoperative bile leakage and anastomotic stricture after liver transplantation treated with magnet compression anastomosis - Sang Jo Han; Sung Ill Jang; Sung Hwan Yoo; Dong Ki Lee (International Journal of Gastrointestinal Intervention, 2020)
Liver transplantation (LT) is a viable treatment for fatal end-stage liver disease. Anastomotic bile leakage and anastomotic stricture are considered as major post-LT complications. Stent insertion by endoscopic retrograde cholangiopancreatography and percutaneous transhepatic biliary drainage is the conventional treatment for post-LT anastomotic biliary stricture. In cases in which these conventional modalities fail, magnet compression anastomosis (MCA) can be applied. We reported a case in which post-LT bile leakage and anastomotic stricture were treated by MCA and using a fully covered self-expandable metal stent (FCSEMS). The FCSEMS was removed 3 months later, at which time the stricture and the leakage had resolved.